The effect of misoprostol with and without letrozole in inducing successful medical abortion - Moghaddaseh Jahanshahi; Maryam Montazeri; Samaneh Mohammadreza Khani Nezhad; Abolfazl Kargar Shouraki (Mashhad University of Medical Sciences, 2023)
Introduction: The pharmacological approach of abortion is a safe and effective alternative to surgical procedures that is associated with a high level of patient's satisfaction. The present study was performed with aim to evaluate the effect of misoprostol with and without letrozole in the treatment of successful medical abortion and its relationship with BHCG titration level and cervical length. Methods: This two-group randomized clinical trial study was performed in 2021 on 168 pregnant women under 18 weeks of gestation who were candidates for termination of pregnancy. The patients were randomly divided into two groups: A (misoprostol and letrozole) and B (misoprostol and placebo). Initial tests, βHCG titration, ultrasound and cervical length were performed for all patients on the first day of hospitalization. After receiving the drug, all patients underwent ultrasound on the fifth day to evaluate complete abortion and removal of pregnancy residues. Data were analyzed by SPSS software (version 22) and Chi-square, independent t and logistic regression tests. P<0.05 was considered statistically significant. Results: The results showed that misoprostol + letrozole had a more successful abortion rate than misoprostol + placebo (88.1% vs. 59.5%). Increased cervical length was associated with a higher probability of miscarriage (P <0.001), while BHCG titration did not show a predictive role in induction of abortion (p>0.05). Conclusion: Adding letrozole to misoprostol for inducing abortion leads to an increase in the percentage of successful abortion and a reduction in the use of curettage.